The crystal structure of 1-propyl-2-nitro-imidazole oxide, C6H9N3O3 - Jun Yuan; Bingheng Wu; Yong Wang; Jianlong Wang; Duanlin Cao; Lizhen Chen (Zeitschrift für Kristallographie - New Crystal Structures)
C6H9N3O3, monoclinic, P21/n (no. 14), a = 9.5584(4) Å, b = 6.7828(3) Å, c = 12.8337(6) Å, β = 103.8810(10)∘, V = 807.74(6) Å3, Z = 4, Rgt(F) = 0.0455, wRref(F2) = 0.1166, T = 170.0 K.